Nitrogen rate, irrigation and rainfall impacts on groundwater nitrate levels in sandy coastal golf courses. Issue 1 (8th April 2022) - Petrovic, A. Martin; Cambareri, Thomas C.; Barnes, LaJan; Cohen, Stuart
Abstract: There have been concerns over fertilizer nitrogen (N) applied to turfgrass areas affecting groundwater quality in sandy coastal areas since the 1970s . Extensive amount of small‐scale research studies has determined the major factors that contribute to excessive nitrate‐N leaching from turfgrass ecosystems. There are limited data on large‐scale groundwater monitoring of turfgrass sites, such as golf courses, which are related to management inputs. There are land‐use regulations limiting the amount of fertilized turfgrass in coastal area in the United States which assume a linear relationship between the amounts of N applied and leached. The purpose of this study is to evaluate the long‐term impact of yearly variations in N application rate, irrigation amounts, and seasonal precipitation on groundwater quality on golf courses in critical groundwater recharge areas. Two golf courses, The Bridge and Sebonack Golf Club, in this study are in eastern Long Island, NY with systematic groundwater monitoring for NO3 –N. Each golf course follows best management practices (BMP) including limitations on amount, rate, source and timing of N applications as well as controlled irrigation based on on‐site evapotranspiration measurements. The results of this study clearly show that on golf courses in sandy critical groundwater recharge areas that follow BMP, the amount of N applied is not related to NO3 –N levels in groundwater. Rainfall amounts more closely followed NO3 –N levels in groundwater, thus abnormally high rainfall can result in higher NO3 –N levels. Implementing fertilizer BMP can be very effective in protecting groundwater quality. Core Ideas: There is need for large‐scale, real‐life groundwater quality data relating to fertilization practices. When BMP are followed, the amount of N applied did not relate to groundwater quality. Growing season precipitation was related to nitrates in groundwater. Irrigation based on ET did not relate to nitrate levels in groundwater.